2011
DOI: 10.1037/a0021083
|View full text |Cite
|
Sign up to set email alerts
|

Cultural conditioning: Understanding interpersonal accommodation in India and the United States in terms of the modal characteristics of interpersonal influence situations.

Abstract: We argue that differences between the landscapes of influence situations in Indian and American societies induce Indians to accommodate to others more often than Americans. To investigate cultural differences in situation-scapes, we sampled interpersonal influence situations occurring in India and the United States from both the influencee's (Study 1) and the influencer's (Study 2) perspectives. We found that Indian influence situations were dramatically more likely than U.S. situations to feature other-servin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
76
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(81 citation statements)
references
References 79 publications
(81 reference statements)
5
76
0
Order By: Relevance
“…Past studies found that people acquire knowledge of descriptive norms through vicarious learning (Savani et al, 2011). Extending these findings, our results indicate that descriptive norms can be formed through implicit learning: The perceivers absorb information about the frequency of occurrence of a certain stimulus event in the environment as they go about their daily business without giving conscious attention to memorizing and learning per se (Seger, 1994), and infer from their idiosyncratic experiences with the stimulus event how well known it is to others.…”
Section: Implicit Learning Of Perceived Descriptive Normsmentioning
confidence: 51%
See 1 more Smart Citation
“…Past studies found that people acquire knowledge of descriptive norms through vicarious learning (Savani et al, 2011). Extending these findings, our results indicate that descriptive norms can be formed through implicit learning: The perceivers absorb information about the frequency of occurrence of a certain stimulus event in the environment as they go about their daily business without giving conscious attention to memorizing and learning per se (Seger, 1994), and infer from their idiosyncratic experiences with the stimulus event how well known it is to others.…”
Section: Implicit Learning Of Perceived Descriptive Normsmentioning
confidence: 51%
“…For example, one can consult statistics to learn the percentage of business leaders who are women. Aside from explicit learning, people also acquire knowledge of the descriptive norms in a culture through observational learning (Savani, Morris, Naidu, Kumar, & Berlia, 2011). In interpersonal situations that call for decisions, other people's responses provide rewards or punishments.…”
Section: Experiential Foundations Of Perceived Descriptive Normsmentioning
confidence: 99%
“…It is evident in the study conducted by. 37 In this study, Indian and European students were shown a large no of interpersonal situations relevant to their culture. Results indicated that both types of situation and individual tendencies together played a crucial role in students" reactions pertaining to cultural differences.…”
Section: Sources Of Cultural Variation In Emotion Regulationmentioning
confidence: 99%
“…Relatedly, accommodating to others' influence attempts, especially when the influencer is believed to have an other-serving motive (e.g., helping the target solve a problem), is normative in collectivist cultures (Savani, Morris, Naidu, Kumar, & Berlia, 2011). Therefore, in a collectivisit context, people may be more receptive to advice and are less likely to expect an advice giver to prepare the ground for advice with problem inquiry and analysis.…”
mentioning
confidence: 99%